Compressed air massage: repeated treatment causes less muscle oedema than a single treatment - M. A. Gregory; M. Mars (AOSIS, 2007)
Compressed air massage is a new treatment modality that has been shown to cause skeletal muscle capillary dilation for up to 24 hours after a single treatment and significantly hastens healing of diabetic ulcers. This study compares the effect of one treatment of a single muscle group, with repeated treatments of several muscle groups. Methods: Four vervet monkeys underwent one, 15 min, treatment of compressed air massage at 1 Bar, to the tibialis anterior muscle and four animals received similar treatment to the whole lower leg on three consecutive days. The tibialis anterior of the treated and untreated limbs was biopsied immediately after the final treatment. Muscle fibre diameters were measured from 1µm thick toluidine blue stained resin embedded sections using light microscopy and computerized image analysis software. Results: For treatment of the whole lower limb, the mean fibre diameter increased by 6.0% from 47.31±13.4µm (95%CI:46.47-48.16) in control biopsies to 50.14±13.93µm (95%CI:49.26-51.02) in treated muscle (p<0.001). Treatment of a single muscle showed an increase in diameter of 11.3%, from 48.21±12.68µm (95%CI:47.31-49.11) to 53.63+14.29µm (95%CI:52.61-54.66 (p<0.001). Treatment of a single muscle caused significantly more oedema than treatment of the whole limb (p<0.001). Conclusions: Repeated treatment causes skeletal muscle oedema, and this appears to be dose related. Skeletal muscle oedema after three treatments is less than after a single treatment. Further studies on the use of compressed air massage on injured muscle are warranted.